2002
DOI: 10.1073/pnas.062630899
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the OpcA integral membrane adhesin from Neisseria meningitidis

Abstract: OpcA is an integral outer membrane protein from Neisseria meningitidis, the causative agent of meningococcal meningitis and septicemia. It mediates the adhesion of N. meningitidis to epithelial and endothelial cells by binding to vitronectin and proteoglycan cell-surface receptors. Here, we report the determination of the crystal structure of OpcA to 2.0 Å resolution. OpcA adopts a 10-stranded ␤-barrel structure with extensive loop regions that protrude above the predicted surface of the membrane. The second e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 42 publications
1
55
1
Order By: Relevance
“…A closer examination of the environment surrounding these two Tyr residues reveals that they form part of a pocket of hydrophobic residues formed by association of Leu-66, Leu-81, Pro-82, Ile-123, Leu-171, and Ile-237 from loops 2-5 ( Fig. 4C) (34). To assign the source of the fluorescence from OpcA, Y169F and Y218F mutations were introduced into OpcA, and the fluorescence spectra of these mutated proteins were compared with wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A closer examination of the environment surrounding these two Tyr residues reveals that they form part of a pocket of hydrophobic residues formed by association of Leu-66, Leu-81, Pro-82, Ile-123, Leu-171, and Ile-237 from loops 2-5 ( Fig. 4C) (34). To assign the source of the fluorescence from OpcA, Y169F and Y218F mutations were introduced into OpcA, and the fluorescence spectra of these mutated proteins were compared with wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of OpcA has shown that the protein adopts a 10-stranded ␤-barrel structure, with extensive loop regions that protrude above the surface of the outer membrane (34). The five external loop regions pack together to form a deep crevice ϳ8 Å wide, 22 Å long, and 11 Å deep, which could form a binding site for saccharide ligands.…”
mentioning
confidence: 99%
“…In fact, the crystal structures of OpcA (26) and NspA (35), two outer membrane proteins of meningococci inducing bactericidal antibodies, showed that they are composed of transmembrane beta barrels containing surface-exposed loops, often with variable sequences, where the bactericidal epitopes are located. In the case of GNA 1870, secondary-structure prediction analysis shows that it is a lipoprotein with a predicted globular architecture consisting of similar proportions of alpha helices and beta strands, a structure very different from those of OpcA and NspA.…”
Section: Discussionmentioning
confidence: 99%
“…An 18-␤-strand porin has also been suggested (10,33). While ␤ barrel proteins with 8 ␤-strands, such as E. coli OmpX (29), Neisseria meningitidis NspA (28), and Comamonas acidovorans Omp21 (2), and a 10-␤-strand protein, OpcA, of N. meningitidis (19), have been suggested to serve as outer membrane anchors rather than forming pores (2,12), the proteoliposome swelling data presented here suggest that the 12 ␤-strands of P28 and OMP-1F form pores. Confirmation of the secondary structure of P28 and OMP-1F awaits crystal structure analysis.…”
Section: Discussionmentioning
confidence: 99%